Herpes Simplex Virus Colitis in a Patient with Newly Diagnosed Crohn's Disease. (14th June 2018) - Jafri, H.; Kalina, D. R.; Aziz, T.; Serrano, P. E.; Haider, S.
Abstract : Herpesvirus colitis is a known cause of morbidity and mortality amongst immunosuppressed individuals. We present a case of HSV colitis following a diagnosis of Crohn's Disease and methylprednisolone therapy. Diagnosis was confirmed by immunohistochemical staining and supported by polymerase chain reaction (PCR) of cutaneous vesicles. The patient recovered following three weeks of acyclovir.